A Calculation Method of Dynamic Parameters of Rotating Arm Bearings Considering the Synthetic Clearance - Xuan Liang; Wan Zefu; Yi Yuanyuan; Hong Wenxiong (Jixie chuandong)
The rotating arm bearing is a key component of RV reducers, and its dynamic parameters directly affect the overall performance of RV reducers. Thus, taking the rotating arm bearing of RV reducers as the research object and considering the geometric parameters of the rotating arm bearing and the change of physical parameters under the working condition, a dynamic calculation model of the rotating arm bearing is established. The relationship between the bearing clearance, oil film thickness, temperature rise and the synthetic clearance of the rotating arm bearing is analyzed. The influence of the bearing clearance on the time-varying support stiffness of the rotating arm bearing under different working conditions is obtained by numerical calculation. With the decrease of the synthetic clearance, the radial support stiffness of the bearing tends to be stable. The results show that when considering the synthetic clearance of the rotating arm bearing, the radial support stiffness decreases by 9.7%, so the influence of the synthetic clearance of the rotating arm bearing on the dynamic performance of the system cannot be ignored.